Bentangan Imaginer: Reinvokasi Memori pada Gangguan yang Ditimbulkan oleh Kecerdasan Buatan - Durahman, Deden Hendan; Piliang, Yasraf Amir; Damajanti, Irma; Langi, Armein Z.R. (Journal of Visual Art and Design, 2025)
The rise of generative AI has significantly transformed the creative process, altering artistic workflows and redefining the human role in artmaking. While some artists resist this shift, engaging with machine intelligence has become increasingly inevitable in today’s digital landscape. This paper explores the disruptive impact of artificial intelligence on artistic practices and how such disruption may benefit rather than hinder creativity. Grounded in Jean Baudrillard’s concept of the hyperreal—particularly his theory of third-order simulation—it examines how AI generates realities that never existed but are perceived as real. These pseudo-realities challenge traditional notions of authenticity and memory in art. Through a performative research method and interdisciplinary approach, the author proposes the concept of ‘re-invocation’—a process of reclaiming the authority of human memory in collaboration with AI. This process is structured in iterative stages involving both human intention and algorithmic intervention. The study demonstrates that incorporating non-human memory has become an unavoidable aspect of art production in the generative AI era. Ultimately, it argues that re-invoking human memory through AI collaboration may offer a critical and innovative foundation for contemporary artistic expression.